Triggering Earthquakes in Science, Politics and Chinese Hydropower: A Controversy Study - Louise Lyngfeldt Gorm Hansen (Copenhagen Business School (CBS), 2017)
This thesis conducts a controversy study focusing on the intermingling of political considerations and emerging science in a controversy over whether or not the Zipingpu dam in China's Sichuan Province caused the magnitude 7.9 Wenchuan earthquake on May 12th 2008. The 2008 Wenchuan earthquake was one of the deadliest, costliest and biggest earthquakes in China in three decades. Over 90,000 people died, went missing or were presumed dead, and economic damage was estimated at over 100 billion US dollars in 2013. For scientists to suggest that such an unfathomable disaster could have been man-made was controversial to say the least. Not only because the root cause of the earthquake pointed to was a dam, and dam projects are inherently rife with conflict, but also because the Zipingpu dam was itself a high priority project for the Chinese central government and the Sichuan Province.
hdl:10398/9562
Keywords: 650